2022
DOI: 10.22190/fupes220218006v
|View full text |Cite
|
Sign up to set email alerts
|

Validnost I Pouzdanost Testa Za Procenu Vremena Reakcije I Brzine Kretanja U Odbrambenom Košarkaškom Stavu

Abstract: The aim of the present study was to examine the content validity and reliability of the newly developed Reaction Time and Defensive Slide Test (RTADST). Thirty-six female basketball players were recruited from three professional State Basketball league of Bosnia and Herzegovina clubs (age: 18.81 ± 2.58 years) who completed three separate trials of the RTADST with each trial consisting of fast shuffling movements left and right.  Each athlete performed the test 3 times in one day, and repeated testing was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Thus, in the systematic review by Clemente et al [ 13 ], 21 studies were identified, of which 8 focused on tactical tests (e.g., FUT-SAT), 10 on technical tests (e.g., Loughborough Soccer Passing Test) and 3 on tests concurrent with physical aspects (e.g., MT5M). In other sports (e.g., basketball) there is an amalgam of instruments with different purposes, such as the influence of contextual variables on tactical thinking [ 14 ], the player discrimination by position according to physical–technical execution patterns [ 15 ] or the relevance of physiological parameters [ 16 ]. In other sports such as rugby [ 17 ], water polo [ 18 ] and ice hockey [ 19 ], tools based on observational methodology have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the systematic review by Clemente et al [ 13 ], 21 studies were identified, of which 8 focused on tactical tests (e.g., FUT-SAT), 10 on technical tests (e.g., Loughborough Soccer Passing Test) and 3 on tests concurrent with physical aspects (e.g., MT5M). In other sports (e.g., basketball) there is an amalgam of instruments with different purposes, such as the influence of contextual variables on tactical thinking [ 14 ], the player discrimination by position according to physical–technical execution patterns [ 15 ] or the relevance of physiological parameters [ 16 ]. In other sports such as rugby [ 17 ], water polo [ 18 ] and ice hockey [ 19 ], tools based on observational methodology have also been developed.…”
Section: Introductionmentioning
confidence: 99%